Association Between Waist Circumference and Cardiorespiratory Fitness in Adolescents and Young Adults: A Narrative Review - Herlangga Ditama; Khoirul Ima; Rachma Hidana (Jurnal Kolaboratif Sains, 2026)
Central obesity and low cardiorespiratory fitness (CRF) are increasingly recognized as important health concerns among adolescents and young adults. Waist circumference (WC) is a simple and practical indicator of central obesity, while CRF is a key marker of cardiovascular and metabolic health. This review aimed to examine the association between waist circumference and cardiorespiratory fitness in adolescents and young adults. A narrative review was conducted using studies retrieved from PubMed and ScienceDirect. Articles published between 2016 and 2026 were screened according to predefined eligibility criteria. A total of 12 studies involving adolescents and young adults were included. The selected studies evaluated waist circumference as a measure of central obesity and cardiorespiratory fitness assessed through VO₂max or validated field-based fitness tests. Findings were synthesized descriptively to identify patterns in the relationship between waist circumference and cardiorespiratory fitness. Current evidence consistently indicates that a larger waist circumference is associated with lower cardiorespiratory fitness. Individuals with greater central adiposity generally exhibit lower CRF levels. However, the magnitude of this association may vary according to factors such as sex, physical activity levels, and the methods used to assess these variables. Given its simplicity and accessibility, waist circumference can serve as a practical approach for identifying cardiometabolic risk at an early stage when combined with cardiorespiratory fitness assessment in adolescents and young adults